Analisis Materi dan Metode Sintaksis Arab dalam Kitab An-Nahwu Al-Wadhih - Andi Holilulloh; Mujawir Sayyid Mujawir Sakran; Wail As-Sayyid (Institut Agama Islam Negeri Metro, 2020)
Arabic is now difficult to learn, both by Arab people ('arabi) and also by non-Arabs (a'jami), so the kitab of an-Nahwu al-Wadhih is the right answer for the development of Arabic in various countries including Indonesia. . This research uses qualitative methods and is a library research. The results of this study indicate that the kitab of an-Nahwu al-Wadhih can use the inductive method (at-thariqah al-istiqraiyyah), namely concrete examples and the facts are described in the first, followed by understanding and conclusions (generalization). The kitab of an-Nahwu al-Wadhih is the right answer for the development of Arabic in various countries including Indonesia, hopefully with the presence of this book it is able to correct Arabic anomalies and is able to strongly maintain the existence of Arabic. The Kitab of an-Nahwu al-Wadhih juz I consists of seventeen rules, from rule 1 to 4 it begins with a discussion of al-kalam, while in juz II, the kitab of an-nahwu al-wadhih consists of 33 rule. begins with rules regarding the discussion of Arabic morphology, namely the division of final and final mu'tal fi'il shahih and for juz III, the kitab of an-nahwu al-wadhih consists of 28 rules beginning with the rules of mubtada khabar.